Benefits of risk‐adapted and mould‐specific antifungal prophylaxis in childhood leukaemia. (4th July 2020) - Meryk, Andreas; Kropshofer, Gabriele; Hutter, Julia; Fritz, Josef; Salvador, Christina; Lass‐Flörl, Cornelia; Crazzolara, Roman
Summary: Fluconazole is one of the most commonly used drugs for antifungal prophylaxis in childhood leukaemia. However, its interaction with vincristine may induce neuropathy and the emergence of antifungal drug resistance contributes to substantial mortality caused by invasive fungal infections (IFIs). In a retrospective single‐centre study, we compared tolerability and outcome of different antifungal prophylaxis strategies in 198 children with acute leukaemia (median age 5·3 years). Until 2010, antifungal prophylaxis with fluconazole was offered to most of the patients and thereafter was replaced by liposomal amphotericin‐B (L‐AMB) and restricted to high‐risk patients only. Vincristine‐induced neurotoxicity was significantly reduced under L‐AMB, as the percentage of patients with severe constipation decreased (15·4% vs. 3·7%, before vs. after 31 December·2010, P  = 0·01) and stool frequency increased by up to 38% in polyene‐treated patients ( P  = 0·005). Before 2011, 10 patients developed confirmed IFIs, most of them were infected with Aspergillus species. After risk adaption in 2011, IFIs were completely prevented ( P  = 0·007). L‐AMB prophylaxis is beneficial in childhood leukaemia patients, as it offers effective antifungal activity with improved tolerability as compared to fluconazole. The potential impact of our risk‐adapted antifungal treatment should be included in current prophylaxis guidelines for childhood leukaemia.